Professional quality of life and job satisfaction among nurses working at tertiary hospitals in central Ethiopia - Sentayehu Admasu Saliya; Taye Mezgebu Ashine; Asnakech Zekiwos Heliso; Getachew Ossabo Babore; Bethelhem Birhanu; Awoke Girma Hailu (BMC, 2024)
Abstract Background Professional quality of life is a crucial aspect of healthcare professionals' well-being and job satisfaction. Job satisfaction, on the other hand, encompasses fulfillment of desired needs within the work environment, happiness or gratifying emotional response towards working conditions, and job values or equity. Existing literature tends to address job satisfaction and professional quality of life separately, overlooking their interconnectedness, especially within the unique context of Ethiopia. This study aimed to assess nurses' professional quality of life and job satisfaction. Methods A descriptive cross-sectional study was conducted from September 1-30 2023 among 420 nurses using a structured questionnaire. The study participants were recruited by simple random sampling. Multiple linear regressions were used to identify factors associated with outcome variables. Results The study involved 420 nurses, with 407 completing the questionnaire, yielding a 96.68% response rate. The findings revealed varying levels of professional quality of life. Specifically, 258 participants (63.4%) exhibited low compassion satisfaction, while 271 (66.6%) and 266 (65.4%) experienced average levels of burnout and secondary traumatic stress, respectively. Job satisfaction was moderate to high for 55% of the participants. As the finding of this study indicates, there is a positive correlation between compassion satisfaction and job satisfaction in nursing. The study also identified predictors for job satisfaction, compassion satisfaction, and compassion fatigue, such as marital status, education, and experience. Conclusion The majority of participants reported a medium level of compassion satisfaction, with a significant proportion experiencing moderate to high levels of compassion fatigue. Although more than half of the participants had moderate to high job satisfaction, there were still low levels of satisfaction. The study recommends developing targeted training programs, implementing workplace policies, and designing initiatives to enhance education, experience, and compassion satisfaction.